Weakly Periodic Gibbs Measures in the HC-Model for a Normal Divisor of Index Four - Khakimov, R. M. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We study an HC-model on a Cayley tree. Under certain restrictions imposed on the parameters of the HC-model, we prove the existence of weakly periodic (nonperiodic) Gibbs measures for a normal divisor of index four.